ANALYSIS OF TURBIDITY LEVEL OF COASTAL WATERS BASED ON THE SUSPENDED SOLIDS IN CILETUH BAY AREA, SUKABUMI REGENCY, WEST JAVA - Marwaiffah Alis, Fauzia
Total suspended solids (TSS) represent the measure of organic and mineral particles moving in water. TSS measurements can also be used to measure erosion rates, and relate to the transfer of nutrients, metals, industrial and agricultural chemicals through water. Increase in TSS content can contribute to an increase in the level of turbidity in its waters. Ciletuh Beach in Sukabumi Regency, West Java is one of the tourist destinations in the Ciletuh Geopark which is surrounded by two rivers. Therefore, this study was conducted to determine the level of turbidity on the Ciletuh beach based on the TSS content in its waters and to assess the quality of water along the Ciletuh coast. The study was conducted using the gravimetric method through random sampling of water at three stations, followed by TSS testing. The results showed that the coast of Ciletuh has turbid waters with a higher level of turbidity at low tide, with an average TSS value of 74 mg/L at low tide and 45 mg/L when sea water is at high tide. Based on sea water quality standards, all sampling stations in Ciletuh coastal waters did not meet the quality standards for the marine biota category of coral species and marine tourism, while the category of mangrove type of marine biota is still fulfilled in the first and second stations.